Socio-Demographic Factors as Moderators of Attitude Towards Coping Among Cancer and Cardiac Patients (Journal of Life and Earth Science, 2014)
The study was designed to explore the attitude towards coping of cancer and cardiac patients as related to certain socio-demographic factors like gender and SES. Purposively selected 360 respondents constituted the sample of the present study. Attitude towards Coping Scale (Rahman, 2010) was used for the collection of data. The sample was equally divided into three categories (cancer. cardiac, normal) on the basis of type of individuals (N=120 for each category).Again they were equally subdivided into male and female on the basis of gender (N=60 for each group).Each category was again equally subdivided into lower middle and upper middle on the basis of SES (N=30 for each group). Results analyzed through ANOVA revealed that the main effects for type of individuals, gender and SES were statistically significant. That is, both cancer and cardiac patients expressed lower coping attitudes as compared to normal individuals, females expressed lower coping attitudes as compared to males and lower middle SES individuals expressed lower coping attitudes as compared to upper middle SES. Again the two way interactions between type of individuals and gender, and type of individual and SES were statistically significant. DOI: http://dx.doi.org/10.3329/jles.v7i0.20121 J. Life Earth Sci., Vol. 7: 51-60, 2012